Abducent nerve palsy as a rare sequela of temporal bone fracture: a case report - Lim, Walter Yung Chwen; Teh, Hui Mon; Rozhan, 'Atikah (Elsevier, 2026)
Temporal bone fractures can be classified into longitudinal, transverse, or mixed types based on their orientation relative to the long axis of the petrous part of the temporal bone. They can also be categorized as otic capsule-sparing or otic capsule-violating. These fractures commonly present with clinical features such as hearing loss, otorrhagia (ear bleeding), cerebrospinal fluid (CSF) otorrhea, balance disturbances, and facial asymmetry. Physical signs such as Battle's sign, hemotympanum, conductive hearing loss, and facial nerve palsy often indicate a temporal bone fracture.1 However, isolated abducens nerve (cranial nerve VI) palsy secondary to temporal bone fracture is extremely rare. A review of the literature revealed only two reported cases of isolated abducens nerve palsy associated with temporal bone fracture following head trauma.2,3 Most reported cases present with concomitant facial nerve involvement.